Strength of hierarchically porous ceramics: Discrete simulations on X-ray nanotomography images. (1st March 2016) - Roussel, Denis; Lichtner, Aaron; Jauffrès, David; Villanova, Julie; Bordia, Rajendra K.; Martin, Christophe L.
Abstract: Porous ceramic samples were processed either by freeze-casting or by slip-casting with pore formers. They were partially sintered to obtain a total porosity in between 44 and 69%. Samples were imaged by X-ray nanotomography with 75 nm resolution. The images, approximately 70 3 to 90 3 μm 3 in size, were merged with randomly packed particles to obtain representative numerical microstructures. The numerical samples were crushed uniaxially using discrete element simulations with appropriate microscopic fracture properties. This revealed anisotropic behavior for freeze-cast samples. Simulated strength values were compared to experimental data, with some consideration given to sample volume. Graphical abstract: